2010
DOI: 10.1007/s11524-009-9431-y
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use with Female Sex Workers among Male Clients in Sichuan Province, China: The Role of Interpersonal and Venue-Level Factors

Abstract: Commercial sex work has re-emerged as a widespread industry since China started economic reforms in the 1980s. This study examined the role of interpersonal and venue-level factors in commercial sex male clients' (CSMCs) condom use with female sex workers (FSWs) in China. Given the heterogeneity of commercial sex industry in China, this study also aimed to explore how these factors function differently by social ranks of commercial sex work frequented by CSMCs. A cross-sectional survey was conducted with 601 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
2
25
2
Order By: Relevance
“…[48][49][50][51] The time period in which these two cohorts were sampled corresponded with increased criminalisation of sex work, which impacted the number and settings of transactional sex. These shifts can have mixed effects.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51] The time period in which these two cohorts were sampled corresponded with increased criminalisation of sex work, which impacted the number and settings of transactional sex. These shifts can have mixed effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, illegal female commercial sex provided an easy path to infidelity (Hong & Li, 2008;Huang, Henderson, Pan, & Cohen, 2004;Jeffreys, 2004Jeffreys, , 2006Pan,1999Pan, , 2000Tucker et al, 2010). The extent to which the rise in commercial sex and extramarital sex could be attributed to rich businessmen who travel or to migrants absent family and community controls remained a matter of debate (Chang, 2008;Chen et al, 2009;Gaetano, 2008;Uretsky, 2008;Yang, Latkin, Luan, & Nelson, 2010;Zhang, 2001;Zheng, 2006Zheng, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, Yang, Latkin, Luan, and Nelson (2010) found that both personal factors and location predicted consistent condom use for women in sex work within lower social ranks. Notably, personal factors did not relate to condom use within middle and upper social ranks.…”
Section: Introductionmentioning
confidence: 91%